KOMODIFIKASI ANAK DALAM PENTAS BUDAYA POPULER - Yunitasari, Yunitasari (Universitas Prof. Dr. Moestopo (Beragama), 2015)
This study aims to learn about the performance and the co-modification of children in Idola Cilik singing contest program on RCTI through text analysis, to determine the background of its production and capitalism whichchanges the value of effectiveness into exchange rate on RCTIâs âIdola Cilikâ program through social cognition analysis, and to find out the interpretation of the Chairman of the National Commission on Child Protection and communication experts on âIdola Ciliklâ singing contest program through social context.This study uses qualitative research methods through Van Dijkâs critical discourse analysis, which includes analysis of the level of text, social cognition and social context.The results showed (1) Based on the analysis of the text, the performance and the co modification of children in the âIdola Cilikâ is actually a result of television media industry as a business institution (RCTI). This has become a commodity, to be bought and sold, and controlled by market mechanisms, through a program rating, which ultimately is profit-oriented. (2) Based on the analysis of social cognition, RCTIâs âIdola Cilikâ programwas created due to the lack of special programs for children. âIdola Cilikâ is a popular culture with instant characteristics and is market oriented. The practice of capitalism is seen in the television industry althoughRCTI as a capitalist is trying to show that exploitation does not happen, by creating a number of provisions, for the sake of achieving their interests, making it look as if it is not they who did the co modification of children. (3) Based on the social context, Idola Ciliklâ has generated positive interpretation, the program can become a means of developing talent and increasing the potential of the children according to children characteristics. There is also a negative interpretation that the program is a form of co modification of children, which leads toexploitation and making it potentially violates the rights of children